Estimates of Foraging Population and Territory of Heterotermes tenuis Colonies using Mark-Release-Recapture (Isoptera: Rhinotermitidae) - Costa-Leonardo, Ana Maria [UNESP]; Casarin, Fabiana Elaine [UNESP]; Ferreira Jr., João [UNESP] (My University, 2003)
Heterotermes tenuis is an important economic pest in São Paulo state. Foraging populations of three field colonies of H. tenuis located on a University campus (UNESP, Rio Claro, SP, Brazil) were characterized. Foraging populations of H. tenuis colonies were calculated using four cycles of a mark-release-recapture program with a weighted mean method. The foraging population sizes of three colonies: A, B and C were 389,313±14,907; 265,589 ±12,635; and 641,600∓12,127; respectively. Foraging biomasses were 0.77 kg in the colony A, 0.51 kg in the colony B and 1.17 kg in colony C. Mean worker biomass was approximately 1.9 mg. Foraging territories occupied an area ranging from 70 m2 to 131 m2 per colony. The maximum linear foraging distance traveled by H. tenuis was 28m.
Keywords: Foraging population; Heterotermes tenuis; Mark-release- recapture; Territory size; Isoptera; Rhinotermitidae